Control of Material Procurement Cost of Enterprises under the Background of the Low-Carbon Economy - Yan Ma (Advances in Materials Science and Engineering)
With the increasing prominence of global warming and serious resource consumption, the low-carbon economy has become a new growth point for the world economy and is widely recognized by all sectors of society. Purchasing cost control management is generally regarded as an applied management discipline with important theoretical, operational, time, and management roles. Due to China’s rapid economic development, high energy consumption, heavy pollution, and high emissions have resulted in catastrophic environmental damage. In recent years, the public’s awareness of environmental protection has increased, and the requirements for enterprises to reduce pollution and energy consumption have increased, and environmental issues have become more and more important in China’s economic development strategy. Based on the background of a low-carbon economy, this article studies the energy consumption of company’s buildings and weights the suppliers of building raw materials. The maximum value, CI value, and CR value of the quality factor were 7.3379, 0.0566, and 0.0429, respectively.